XPD–The Lynchpin of NER: Molecule, Gene, Polymorphisms, and Role in Colorectal Carcinogenesis - Sameer, Aga Syed; Nissar, Saniya (Frontiers in Molecular Biosciences, 2018)
In mammals the bulky DNA adduct lesions known to result in deleterious phenotypes are acted upon and removed from the genomic DNA by nucleotide excision repair (NER) pathway. TFIIH multi-protein complex with its important helicase –Xeroderma Pigmentosum Protein (XPD) serves as the pivotal factor for opening up of the damaged lesion DNA site and carry out the repair process. The initial damage verification step of the TFIIH is in part dependent upon the helicase activity of XPD. Besides, XPD is also actively involved in the initiation steps of transcription and in the regulation of the cell cycle and apoptosis. In this review, we will be exploring the new insights in scientific research on the functioning of the NER pathway, the role of TFIIH as the central complex of NER, the pivotal helicase XPD as the lynchpin of NER and the effects of various single nucleotide polymorphisms (SNPs) of XPD oin its functioning and their consequent role in colorectal carcinogenesis.